Study of association of pancreatitis with enteric fever of age group 1 to 15 years - Dr. Dillip Kumar Das; Dr. Suprabha Shukla; Dr. Mangal Charan Murmu (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Enteric fever is endemic in India. 1% of children up to 17 years of age suffer from Enteric fever. Enteric fever is a systemic disease characterized by fever and abdominal pain caused by the dissemination of Salmonella typhi or S. paratyphi. The term enteric fever includes both typhoid fever and paratyphoid fever. Many case reports of severe acute pancreatitis during salmonellosis have been reported, suggesting that serious pancreatic disease may represent a complication of Salmonella infection.Aim and objective: To find out the frequency of acute pancreatitis considering clinical features, biochemical changes (serum amylase and lipase), and ultra-sonographic evidence of pancreatic involvement in the pediatric population by estimating serum amylase and lipase level in the pediatric population who were admitted with the diagnosis of Enteric fever.Material and Method: The present prospective study was conducted in the S V P PG Institute of pediatrics and SCB Medical College, Cuttack, Odisha, India which is a premier referral institute of eastern India.Result: Overall the proportion of patients with raised levels of serum amylase and lipase in the Enteric fever group was 44.68% (n=21). Comparing these values with the control group shows that the rise in serum amylase and serum lipase levels were statistically more significant (‘p’ value <0.05).Conclusion: Hence, salmonella may be considered as a causative agent of subclinical pancreatitis with biochemical and radiological changes.